Early Detection of Maternal Risk Factors for Stunting in Infants - Iin Setiawati; Selvia Nurul Qomari; Dana Daniati (Fakultas Ilmu-ilmu Kesehatan, 2026)
Stunting can develop while fetus is still in womb and is only visible in infants at two years of age. Indonesia’s stunting rate reached 19.8% in 2024, which is still higher than government's target of below 14%. This study aims to identify maternal risk factors for stunting. This retrospective study applied a quantitative analysis approach. A total of 323 mothers participated in this study, and researchers used Early Detection of Low-Birth-Weight Risk Scorecard (EDBLWRSC) and Dhiana Setyorini Scorecard (DSSC) to collect data. The analyzed using Chi-square tests with an α of 0.05. The results revealed that stunting was associated with parity item of DSSC (ρ = 0.00) and a history of preeclampsia (ρ = 0.00). Meanwhile, obesity was associated with either outcome. Moreover, in EDBLWRSC, anemia was associated with stunting (ρ = 0.00), a history of low birth weight was associated with a higher incidence of low birth weight (ρ = 0.01). The maternal risk variable on DSSC and stunting (ρ = 0.00) had an OR of 2.2 and 3.3, respectively. The EDBLWRSC also revealed a relationship between maternal risk factors and stunting (ρ = 0.00). Therefore, some of maternal risk factors in DSSC and EDBLWRSC are associated with stunting.